Does External Debt Cause Growth? A Comparative Study Of Nigerian And South African Economies - Doorasamy, Mishelle; Adejayan, Adeola Oluwakemi; Nyahuna, Thomas (Journal of Business and Management Review, 2024)
Research Aims:  The purpose of this study is to ascertain the effect of external debt on economic growth and the causal relationship that exists between external debt and growth in South Africa and Nigeria between 1981 and 2022. Design/methodology/approach: To this end, VECM, VAR and pairwise Granger causality were used to analyze the data. on GDP, external debt, debt servicing, government expenditure, and exchange rate.  .  Research Findings:  The results show that the effect of external debt on economic growth is insignificant in the near term, having positive influence in South Africa and negative impact in Nigeria. However, the long-term effects are detrimental and noteworthy in South Africa. Also, the results on causality indicate that, in Nigeria, there is no causal relationship between external debt and economic growth, but in South Africa, there is a unidirectional relationship between GDP and external debt Theoretical Contribution/Originality:  This study concludes that, whereas exchange rates are the primary predictor of economic growth in Nigeria, external debt neither causes nor determines economic growth in South Africa or Nigeria. Rather, causation flows from economic growth to external debt exclusively in South Africa. Therefore, this study recommends that the government of both countries should channel their available resources towards developmental projects that will spur growth. Keywords: External debt, Causality, Growth, Emerging Market, GDP